Novel ERP Evidence for Processing Differences Between Negative and Positive Polarity Items in German - Liu, Mingya; König, Peter; Mueller, Jutta L. (Frontiers in Psychology, 2019)
One unresolved question about polarity sensitivity in theoretical linguistics concerns whether and to what extent negative and positive polarity items are parallel. Using event-related brain potentials (ERPs), previous studies found N400 and/or P600 components for negative and positive polarity violations with inconsistent results. We report on an ERP study of German polarity items. Both negative and positive polarity violations elicited biphasic N400/P600 effects relative to correct polarity conditions. Furthermore, negative polarity violations elicited a P600-only effect relative to positive polarity violations. The lack of a graded N400 effect indicates that both kinds of violations involve similar semantic processing costs. We attribute the increase in P600 amplitude of negative polarity violations relative to positive polarity violations to their different nature: the former are syntactic anomalies triggering structural reanalysis, whereas the latter are pragmatic oddities inducing discourse reanalysis. We conclude that negative and positive polarity violations involve at least partly distinct mechanisms.